Single-photon emission computed tomography as a fundamental tool in evaluation of myocardial reparation and regeneration therapies - Tekieli, Łukasz; Szot, Wojciech; Kwiecień, Ewa; Mazurek, Adam; Borkowska, Eliza; Czyż, Łukasz; Dąbrowski, Maciej; Kozynacka, Anna; Skubera, Maciej; Podolec, Piotr; Majka, Marcin; Kostkiewicz, Magdalena; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Despite unquestionable progress in interventional and pharmacologic therapies of ischemic heart disease, the number of patients with chronic ischemic heart failure is increasing and the prognosis remains poor. Repair/restoration of functional myocardium through progenitor cell-mediated (PCs) healing and renovation of injured myocardium is one of the pivotal directions in biomedical research. PCs release numerous pro-angiogenic and anti-apoptotic factors. Moreover, they have self-renewal capability and may differentiate into specialized cells that include endothelial cells and cardiomyocytes. Uptake and homing of PCs in the zone(s) of ischaemic injury (i.e., their effective transplantation to the target zone) is an essential pre-requisite for any potential therapeutic effect; thus effective cell tracking is fundamental in pre-clinical and early clinical studies. Another crucial requirement in rigorous research is quantification of the infarct zone, including the amount of non-perfused and hypo-perfused myocardium. Quantitative and reproducible evaluation of global and regional myocardial contractility and left ventricular remodeling is particularly relevant in clinical studies. Using SPECT, our earlier work has addressed several critical questions in cardiac regenerative medicine including optimizing transcoronary cell delivery, determination of the zone(s) of myocardial cell uptake, and late functional improvement in relation to the magnitude of cell uptake. Here, we review the role of single-photon emission computed tomography (SPECT), a technique that offers high-sensitivity, quantitative cell tracking on top of its ability to evaluate myocardial perfusion and function on both cross-sectional and longitudinal bases. SPECT, with its direct relevance to routine clinical practice, is a fundamental tool in evaluation of myocardial reparation and regeneration therapies.